Pengaruh Kualitas Layanan dan Penanganan Keluhan terhadap Loyalitas Nasabah dengan Kepuasan sebagai Variabel Intervening (Studi Kasus BPRS Suriyah Cabang Salatiga) - Ratno, Fernaldi Anggadha (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
The purpose of this study was to determine the effect of Quality of Service (X1) and Complaint Handling (X2) to Customer Loyalty (Y) with Satisfaction (Z) as an intervening variable. This study uses quantitative methods because it aims to confirm the dataÂ  obtained in the field with existing theories. Samples were obtained as many as 100 respondents of BPRS Suriyah Salatiga with accidental sampling technique. The data used in this study are primary data with a questionnaire. Data analysis used statistical tests through ttest test, f test, coefficient of determination (R2), instrument test, classical assumption test and Path Analysis test with the help of SPSS version 20. The result of this study indicate that service quality has a positive and significant effect on customer satisfaction, complaint handling has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, complaint handling has a positive and significant effect on customer loyalty, satisfaction has a positive and significant effect on customer loyalty, satisfaction mediates service quality to customer loyalty, and satisfaction mediates complaint handling to customer loyalty.